The Year of the Three Sisters - Book 4 - Cheng, Andrea; Barton, Patrice, 1955- (Boston : HarperCollins Publishers, 2015)
Twelve-year-old Annas friend Andee spearheads a campaign to bring Fan from China to Cincinnati on a year-long cultural exchange, but before Fan even arrives Annas concerned that Andee and Fan are too different to get along.
Keywords: Chinese Americans -- Juvenile fiction; Friendship in children -- Juvenile fiction; Student exchange programs -- Juvenile fiction; Juvenile fiction